Trees response to selective thinning and pruning in Sudanian woodland zone - Assèdé, Eméline Sêssi Pélagie; Biaou, Samadori Sorotori Honoré; Azihou, Akomian Fortuné; Orou, Hidirou; Geldenhuys, Coert Johannes; Chirwa, Paxie Wanangwa (Frontiers in Forests and Global Change, 2023)
Introduction Managing the degradation and loss of Sudanian woodlands to ensure sustainable use for mainly firewood, poles, and timber is receiving increasing attention, and it requires tailored strategies to improve stand productivity. This study determined: (i) tree response (density, recruitment, and height growth) to selective stem thinning and branch pruning; and (ii) tree species that are most affected by selective stem thinning and branch pruning in the Sudanian woodland of Benin. Methods Three homogeneous vegetation units of 80 m × 80 m each were identified, representing the three stages of woodland development (WDS): early and young WDS of 3 and 3–5 years old, respectively, and the advanced to mature secondary WDS of 6–9 years old. Three random blocks of 20 m × 20 m each, subdivided into four 10 m × 10 m treatment plots, were delineated per vegetation unit. Each of these plots was randomly assigned a treatment (T): T1—no thinning and no pruning; T2—30% thinning; T3—60% thinning; T4—100% thinning. Branch pruning was applied to all remaining stems in T2 and T3. Tree species, stem abundance and height of individuals = 1 m were recorded every 6 months in 2015 and 2016. Results and discussion Thinning intensity significantly influence tree density both in WDS 2 and 3 with the 30% thinning showing the best tree density (3355.56 ± 250.19 stems/ha and 3255.56 ± 772.68 stems/ha, respectively). However, more stem recruitment was observed without thinning and pruning (883.33 ± 212.13 stems/ha), and 30% thinning and pruning (383.33 ± 164.99 stems/ha). There was a significant increase in tree height growth both in WDS 2 and 3 with an increasing thinning intensity. The two most affected tree species were Terminalia avicennioides and Pteleopsis suberosa with an average growth in height after 6 months of 105.5 ± 1.05 mm (for 30% thinning and pruning in stage 3), and 61.75 ± 0.67 mm (for 60% thinning and pruning in stage 3), respectively. Overall, moderate stem thinning (30%) at WDS 1 and more severe thinning at WDS 2 and 3 resulted in the best tree height growth and recruitment.